Isolation and identification of alcohol dehydrogenase stabilizing peptides from Alcalase digested chicken breast hydrolysates. (January 2020) - Xiao, Chuqiao; Zhao, Mouming; Zhou, Feibai; Gallego, Marta; Gao, Jie; Toldrá, Fidel; Mora, Leticia
Graphical abstract: Abstract: The effect of chicken hydrolysates (CHs) on alcohol dehydrogenase (ADH) stability was investigated, together with further bioactivity-oriented isolation and identification of CHs. A total of 82 peptides were identified using mass spectrometry in tandem after consecutive separation by size-exclusion chromatography and high-performance liquid chromatography. The identified peptides were then subjected to in silico gastrointestinal digestion and 154 peptides were generated. The potential bioactivity, safety and applicability of the peptides were assessed using multiple predictive programs. A total of 21 among the 154 peptides were predicted to be potentially active with applicability. Four peptides (DPQYPPGPPAF, QKPVL, KPC, and APGH) obtained after in silico digestion were synthesized and validated their activity. Results showed that DPQYPPGPPAF, KPC, and APGH could stabilize ADH in a dose-dependent manner. This study further indicated that chicken hydrolysate could be a novel functional food ingredient in facilitating alcohol metabolism and protection against alcoholic liver injury.